DIGITAL PAYMENTS IN INDIA: PROBLEMS & PROGRESS (INTERNATIONAL JOURNAL OF APPLIED SCIENCE & TECHNOLOGY, 2022)
Nowadays, the digital payment system is a vital aspect of all financial transactions. A cashless society is an economic situation in which we do not utilise actual bank notes and coins as a medium of financial transactions, but instead use digital currency or crypto currency. In India, ICICI Bank was the first to offer online banking services, and Digi Bank is also ahead in terms of digitization of transactional services offered to customers. SBI is a public sector bank that has benefited from digitization.
Keywords: Digital Payments